The iron giant - Bird, Brad .; Warner Bros.; Warner Home Video (Firm). (Burbank Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils)., 2000)
Hogarth Hughes just rescued an enormous robot that fell from the stars to Earth. Now young Hogarth has one very big friend and an even bigger problem: how do you keep a 50-foot-tall, steel-eating giant a secret?
Based on the book "The iron man" by Ted Hughes.
Cinematographer, Steven Wilzbach ; animators, Richard Baneham, Adam Burke, Jennifer Cardon, [et al.] ; art director, Alan Bodner ; editor, Darren T. Holmes ; music, Michael Kamen ; production designer, Mark Whiting
Voices: Jennifer Aniston, Harry Connick, Jr., Vin Diesel, James Gammon, Cloris Leachman, Christopher MacDonald, John Mahoney, Eli Marienthal, M. Emmet Walsh.
MPAA rating: PG
Special features: full-screen and widescreen anamorphic formats; theatrical trailer(s); making-of documentary (22 min.); music video "Cha-Hua-Hua" by Eddie Platt , DVD, Dolby digital.
In English
Keywords: Feature films; Animated films